Properties of Fr-like Th3+ from rf spectroscopy of high-L Th2+ Rydberg ions - Keele, Julie A.; Smith, Chris S.; Lundeen, S. R.; Fehrenbach, C. W. (My University, 2013)
Relative positions of twenty n=28 Rydberg levels of Th2+ with L=9, 10, 11, and 12 were determined with sub-MHz precision using the rf-RESIS (resonant excitation Stark ionization spectroscopy) technique. The pattern of binding energies was analyzed with the effective potential model, modified to account for significant nonadiabatic effects. The analysis yielded measurements of several properties of the Fr-like Th3+ core ion, including the quadrupole moment, Q=0.5931(14) a.u.; hexadecapole moment, Π = −0.69(28) a.u.; g factor, gJ=1.24(48); scalar and tensor dipole polarizabilities, αD,0=15.224(33) a.u. and αD,2 = −5.30(11) a.u.; scalar quadrupole polarizability, αQ,0=60(15) a.u.; and the reduced dipole and octupole matrix elements connecting the ground 5f 2F5/2 level with the low-lying 6d 2D3/2 level, ∣∣⟨2F5/2∣∣∣∣M[1]∣∣∣∣2D3/2⟩∣∣=1.436(2) a.u. and ∣∣⟨2F5/2∣∣∣∣M[3]∣∣∣∣2D3/2⟩∣∣=3.3(1.1) a.u. The measured properties are compared with theoretical predictions.